Unboxing the black box on the dimensions of social globalisation and the efficiency of microfinance institutions in Asia - Hussain, Hafezali Iqbal; Katarzyna, Szczepańska Woszczyna; Kamarudin, Fakarudin; Mohamad Anwar, Nazratul Aina; Mohd Saudi, Mohd Haizam (Instytut Badań Gospodarczych, 2021)
Research background: Microfinance institutions (MFIs) play an important role in alleviating poverty. Thus, MFIs should be efficient in order to ensure that their objectives on social welfare and financial performance can be achieved by identifying the potential determinants, specifically on social globalisation.